Effect of macronutrients and sucrose concentration on in vitro growth of Drosera capensis L. (Droseraceae) plants, and evaluation of six substrates for acclimatization - Jiménez García, Víctor (2011)
The effect of two concentrations of the Murashige and Skoog macronutrients (full and half strength), in combination with three concentrations of sucrose (1.5, 3.0 and 4.5% w/v), was evaluated on the in vitro growth of Drosera capensis plants of two sizes (10-15 mm and 20-25 mm). Additionally, growth of plants of this species was assessed in six substrates seven weeks after being acclimatized to in vivo conditions. The smallest plants grown on the lowest concentration of macronutrients and with 1.5 or 3.0% sucrose, and those on the normal concentration of macronutrients with 1.5% sucrose, exhibited the highest increase in growth during the 15 weeks of evaluation. Perlite, vermiculite, peat moss and the mixture of peat moss with perlite showed highest survival rate and a tendency to increased plant growth during acclimatization. On the contrary, soil, alone or in combination with rice husks, evidenced serious drawbacks, probably due to drainage problems, which caused very low survival and poor growth of plants.